Hukum Produktifitas Zakat Fitrah - Imamul Muttaqin (TAQNIN: Jurnal Syariah dan Hukum, 2019)
So far, zakat productivity has only been focused on zakat mal, the productivity of zakat al-Fitr has not been touched at all by BAZ and LAZ, even though the potential of community economic empowerment through the productivity of zakat fitrah is very large if managed properly and responsibly and if fulfilling certain conditions to produce zakat fitrah, this article will discuss in detail the law of producing zakat fitrah, which is how it stands in Islamic law, whether the productivity of zakat fitrah is justified in Islamic law